Effect of pre-strain on compression mode properties of magnetorheological elastomers - Hossein Vatandoost (Elsevier, 2021)
The effects of pre-strain on compression mode dynamic characteristics of both isotropic and aligned magnetorheological elastomers (MREs) are experimentally investigated considering wide ranges of particle volume fraction (15%, 30%, and 45%), frequency (1–30 Hz), and magnetic flux density (0–750 mT) under different levels of pre-strain (6%, 11%, and 21%). Results exhibited strong dependence of MRE behavior on the pre-strain, which was further coupled with the effects of the particle volume fraction and frequency, and the magnetic field. The elastic and loss moduli of isotropic MREs consistently increased in a nonlinear manner, when pre-strain increased from 6% to 21%, suggesting pre-strain stiffening and pre-strain dampening effects, respectively, while aligned MRE showed dissimilar trends depending on particle volume fraction. Results revealed higher pre-strain effects for isotropic MREs than aligned MREs. The relative MR effect in view of elastic modulus (MRE′) for both types of MREs consistently decreased with increasing pre-strain, while in view of loss factor (MRη) showed the same trend only for aligned MRE. MRη of isotropic MRE generally showed maximum around 11% pre-strain. Results further revealed maximum MRE′, up to 286%, 973% and 2258% for the isotropic MRE, respectively, with volume fraction of 15%, 30% and 45%, and obtained as 320%, 293%, and 386% for aligned MRE. Simple phenomenological models were subsequently proposed to predict the compressive moduli as well as stress-strain hysteresis characteristics of both types of MREs. A reasonably good agreement was observed between the models’ results and the experiment data for the ranges of pre-strain, volume fraction, frequency, and magnetic flux density considered. The developed models can be effectively employed for the development and design of controllable MRE-based adaptive devices operating in compression mode.